Manejo preoperatorio de los adenomas hipofisarios. Lo que un residente de neurocirugía debe conocer - Bourilhon, Facundo; Villalonga, Juan F.; Martínez Font, Agustín; Pailler, José I.; Romano, Adán A.; Campero, Álvaro (Revista Argentina de Neurocirugía, 2021)
Sellar lesions are a pathology with an incidence of 3.2 to 4 / 100.000 and a prevalence of 78 to 94 / 100.000. Normally, 10% of them are incidentalomas and adult patients are in the highest risk group. Because it´s prevalence in the world is currently increasing, it is of extremely importance to study and understand this pathology. In relation to the clinical manifestations, it should be noted that it is one of the few diseases that can manifest through neurological signs and symptoms like bitemporal hemianopsia, endocranial hypertension syndrome due to hydrocephalus, as well as endocrinological syndromes like Cushing’s, acromegaly, amenorrhea-galactorrhea and infertility. One of the most important things to notice is that the treatment success in this pathology comes with the correct diagnosis and characterization of it, for what all patients should have a complete clinical-radiological evaluation. In this study, we establish a guide with concepts and key tools to support the medical personal during a pre-surgical preparation of patients with pituitary adenoma.